Adolescents' perspectives on their treatment as inpatients - Benjamin, Amy (Department of Psychology, 2015)
Adolescent inpatient psychiatric care is an accepted intervention for acute adolescent behavioural and emotional problems, yet little is known about patient experiences of this care. This study explores former patients’ views of the therapeutic factors involved in the treatment they received at Kenilworth Clinic’s Adolescent inpatient unit in Cape Town, South Africa. Twelve ex-patients were interviewed using a semi-structured interview schedule; the interviews were recorded, transcribed and analysed qualitatively using template analysis. In line with Yalom and Leszcz’s (2005) work on the therapeutic factors in group work, some of these therapeutic factors featured as major themes in the interviews, specifically: the imparting of information, universality, group cohesiveness, interpersonal learning and catharsis. Other factors featured minimally or not at all; an attempt is made to understand this as well as the potential value of these factors. In addition to these therapeutic factors, patients generally perceived family sessions as both helpful and difficult. Concerns raised by participants about their treatment experience included underage smoking at the unit, confidentiality in aftercare group and a desire for individual therapy by participants. The recommendations made were for the staff at the unit to maximise the therapeutic space for the factors highlighted as important to the patients, to continue to endeavour to prevent patients without consent from smoking and to use rule-breaking therapeutically as far as possible, and to discuss confidentiality rules and concerns in the aftercare group at every session. Ideas for future research were discussed, these included a questionnaire-based study where both staff and patients rank the therapeutic factors involved in treatment according to perceived value and an outcomes study.